1975
DOI: 10.3109/00365597509139906
|View full text |Cite
|
Sign up to set email alerts
|

Search for Urogenital Tract Infections in Patients with Symptoms of Prostatitis: Studies on Aerobic and Strictly Anaerobic Bacteria, Mycoplasmas, Fungi, Trichomonads and Viruses

Abstract: Seventy-nine patients with symptoms of nonacute prostatitis and 20 healthy volunteers were examined for uro-genital tract infection with bacteria, mycoplasmas, fungi, trichomonads and viruses. No differences in the results of the bacterial cultures were found between the patients and the controls. In only a few cases were established urinary tract pathogens found, but in no instance were these findings reproducible in later specimens. The cultures of the expressed prostatic fluids and the samples of semen gave… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

1981
1981
2012
2012

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(14 citation statements)
references
References 29 publications
(11 reference statements)
0
13
0
1
Order By: Relevance
“…In symptomatic men, common complaints include scanty clear to mucopurulent discharge, dysuria, and mild pruritus or a burning sensation immediately after sexual intercourse (166). Complications associated with trichomoniasis include nongonococcal urethritis, prostatitis, balanoposthitis, urethral disease, and infertility (131,167,197). Pneumonia, bronchitis, and oral infection caused by T. vaginalis have also been documented (132).…”
Section: Trichomonas Vaginalismentioning
confidence: 99%
“…In symptomatic men, common complaints include scanty clear to mucopurulent discharge, dysuria, and mild pruritus or a burning sensation immediately after sexual intercourse (166). Complications associated with trichomoniasis include nongonococcal urethritis, prostatitis, balanoposthitis, urethral disease, and infertility (131,167,197). Pneumonia, bronchitis, and oral infection caused by T. vaginalis have also been documented (132).…”
Section: Trichomonas Vaginalismentioning
confidence: 99%
“…Symptomatic men present with a clear or mucopurulent discharge and dysuria (57,58). Complications associated with T. vaginalis infection include prostatitis, balanoposthitis, epididymitis, and infertility (56,82).…”
Section: Trichomoniasismentioning
confidence: 99%
“…Although Mardh and Colleen (Mardh et al, 1972) suggested that C. trachomatis may be implicated in as many as one third of men with CP, their follow-up studies employing culturing and serologic tests could not confirm C. trachomatis as an etiologic agent in idiopathic prostatitis (Mardh & Colleen, 1975;Mardh et al, 1978). Shortliffe and Wehner (Shortliffe & Wehner, 1986) came to a similar conclusion when they evaluated antichlamydial antibody titers in prostatic fluid.…”
Section: Chronic Prostatitismentioning
confidence: 98%